What do people really think about grief counseling? Examining community attitudes - Breen, Lauren; Croucamp, C.; Rees, Clare (Routledge, 2018)
© 2018, © 2018 Taylor & Francis Group, LLC. To understand why bereaved people who are highly distressed significantly underutilize grief counseling and therapy, we surveyed adults (N = 156) to investigate community attitudes toward grief counseling. Overall attitude was positive and women reported a significantly more positive attitude than men; there were no associations between attitude and age, country of birth, previous counseling, or bereavement experience. After controlling for gender, beliefs and affects explained attitudes toward grief counseling; behavioral responses did not. Targeting beliefs about grief counseling may promote positive attitudes so that people most likely to benefit from intervention will be more likely to seek it.